Tumors of the Central Nervous System, Volume 11 Pineal, Pituitary, and Spinal Tumors - Hayat, M.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Like the ten preceding volumes in the series Tumors of the Central Nervous System, this book is distinguished for its comprehensive approach, its distinguished roster of some 93 contributors representing 8 different countries and its embrace of leading-edge technology and methods. Volume 11: Pineal, Pituitary, and Spinal Tumors concentrates on the diagnosis, prognosis and therapy of four types of tumors, namely Glioblastoma, Meningioma, Schwannoma and Spinal Tumors. The book offers an in-depth survey of a range of new technologies and their applications to tumor diagnosis, treatment and therapy assessment. The contributors explain in thorough detail a range of current and newly developed imaging methods, including molecular imaging and PET scan. Also covered is molecular profiling of brain tumors to select therapy in clinical trials of brain tumors. Discussion includes a review of such surgical treatments as resection and the application of non-invasive stereotactic radiosurgery for treating high-risk patients with brain metastasis. Additional discussion is devoted to tumor seeding.
Preface. I Imaging -- An introduction to brain tumor imaging.-Molecular imaging of brain tumors -- Use of 11c-4dst-pet for imaging of human brain tumors. II Glioma and glioblastoma -- Diffusion tensor magnetic resonance imaging-based tractography for glioma surgery -- Angiocentric glioma, pilomyxoid astrocytoma, and Pituicytoma: new entities in the world health organization classification -- Diffuse intrinsic pontine gliomas in children: treatment (an Update) -- Gliomatosis cerebri: implications of genetic findings -- Impact of bevacizumab chemotherapy on glioblastomas -- Glioblastoma microvesicles transport rna and proteins Promoting tumor growth -- Microrna in the pathophysiology of glioblastoma -- Surgical management of incidental low-grade gliomas. III Stereotactic radiosurgery -- Stereotactic radiosurgery for the treatment of brain metastases -- Local control of low-volume brain metastases using stereotactic radiosurgery -- Tumor seeding after stereotactic brain biopsy -- Intracranial stereotactic radiosurgery in high risk patients with metastases from radioresistant primary tumors -- Brain metastases: treatment with stereotactic iodine-125 brachytherapy -- Stereotactic radiosurgery for skull base meningiomas. IV Spinal cord tumors -- Pediatric spinal cord tumors -- Radiosurgery for intramedullary spinal cord tumors -- Novalis spinal radiosurgery -- Etiology and outcomes of pediatric spinal cord tumors. V Meningioma -- Selection of elderly meningioma patients for surgery using a Clinical-radiological grading system as a predictor of outcome -- Cranial meningioma in neurofibromatosis type 2 patients: role of mutations -- Classification of meningioma using immunogenic antigens -- Treatment of benign meningiomas using radiosurgery -- Necrotic rhabdoid meningiomas: histopathological diagnosis. VI Schwannomas. 27 Multiple schwannomas: diagnosis and treatment -- Treatment of patients with vestibular schwanommas using gamma knife radiosurgery -- Schwannomas in the craniocervical region: complete surgical removal -- Cranial base surgery of hypoglossal schwannomas. Index.
Keywords: Medicine; Oncology; Biomedicine; Cancer Research; Oncology; Biomedicine general